Merrywood Plantation (Jamaica : [Publisher not identified], 1826)
Diagram of Merrywood Plantation, containing 1410 acres, the dotted lines representing six equal shares. Resurveyed by the desire of John Morris and Joseph Ridley in September 1826 by Philip Angell.
Keywords: Maps; St. Elizabeth (Jamaica) -- Maps